2021
DOI: 10.3389/fonc.2021.702908
|View full text |Cite
|
Sign up to set email alerts
|

Controlling Nutritional Status Score Before Receiving Treatment as a Prognostic Indicator for Patients With Urothelial Cancer: An Exploration Evaluation Methods

Abstract: IntroductionThis meta-analysis aims to assess whether the Controlling nutritional status (CONUT) score before treatment can be an independent predictor of the prognosis of patients with urothelial cancer (UC).MethodsThe system searches Web of Science, PubMed, MEDLINE, China National Knowledge Infrastructure (CNKI), and Cochrane Library, and the search time is up to April 2021. Use STATA 16.0 and Engauge Digitizer 4.1 software for data processing and statistical analysis.ResultsA total of 8 studies were include… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 50 publications
(84 reference statements)
0
6
0
Order By: Relevance
“…In a study of 94 patients with non-invasive BC, the CONUT score obtained before treatment was correlated with poor survival and recurrence ( 41 ). In another meta-analysis examining 4,044 patients with metastatic urothelial carcinoma, pretreatment CONUT score was correlated with poor survival ( 42 ).…”
Section: Discussionmentioning
confidence: 99%
“…In a study of 94 patients with non-invasive BC, the CONUT score obtained before treatment was correlated with poor survival and recurrence ( 41 ). In another meta-analysis examining 4,044 patients with metastatic urothelial carcinoma, pretreatment CONUT score was correlated with poor survival ( 42 ).…”
Section: Discussionmentioning
confidence: 99%
“…conducted a meta-analysis that included 2601 patients, revealing a significant association between high CONUT score and poor prognosis in patients with colorectal cancer ( 10 ). A meta-analysis involving eight studies has demonstrated the correlation between high CONUT score and OS, cancer-specific survival, and RFS in patients with urothelial carcinoma who have undergone systematic treatment ( 34 ). A meta-analysis conducted by Zhang et al.…”
Section: Discussionmentioning
confidence: 99%
“…One study included all urinary carcinoma, include renal cell carcinoma and testicular carcinoma [36]. The other two studies only focus on bladder carcinoma [37,38], ignoring the similarities in morphological structure and carcinoma biology of urinary transitional epithelium [39]. This similarity not only Forest plot and meta-analysis of the relationship between OS and SII…”
Section: Discussionmentioning
confidence: 99%